Strategic Innovative Marketing and Tourism (Springer Nature, 2024)
This open access book presents the latest findings of researchers from around the globe who presented their work at the 10th international conference of Strategic Innovative Marketing and Tourism (ICSIMAT) in 2023. It provides an up-to-date information and discusses current trends, issues, and debates, both theoretical and practical research, on strategic innovative marketing and tourism and applications from social media and emerging technologies in Artificial Intelligence and the Internet of Everything. Topics covered in the chapters include social media in marketing and tourism hospitality, culture, strategic tools, and techniques employed and implemented by some of the top research laboratories in the world to the industry. This book brings together work from both academia and industry and continues the successful impact of the previous years' conference on the academic discussion of the topics.